Kualiti perkhidmatan, kepuasan pelanggan dan kesetiaan pelanggan Perbadanan Perpustakaan Awam Terengganu: Kajian konseptual - Mahmood, Kamarulzaman; Mat Ali @ Salim, Nor Azman; Mohamad, Mahadzirah (Persatuan Pustakawan Malaysia, 2015)
This paper discusses and reviews the literature and ultimately propose a conceptual framework linking service quality, customer satisfaction and customer loyalty within the Terengganu State Public Library (PPAT). It is designed to understand how service quality and customer satisfaction are perceived as sources of loyalty by library’s customers. This study will use the LibQual questionnaire instruments as the main survey tool to collect information from the respondents. The findings of this study are expected to provide a reference and a bench mark to the public library’s stakeholders in order to enhance their services quality.